2020
DOI: 10.1002/jcp.29758
|View full text |Cite
|
Sign up to set email alerts
|

PCTR1 improves pulmonary edema fluid clearance through activating the sodium channel and lymphatic drainage in lipopolysaccharide‐induced ARDS

Abstract: Acute respiratory distress syndrome (ARDS) is a lethal clinical syndrome characterized by damage of the epithelial barriers and accumulation of pulmonary edema fluid. Protectin conjugates in tissue regeneration 1 (PCTR1), an endogenously produced lipid mediator, are believed to exert anti‐inflammatory and pro‐resolution effects. PCTR1 (1 µg/kg) was injected at 8 hr after lipopolysaccharide (LPS; 14 mg/kg) administration, and the rate of pulmonary fluid clearance was measured in live rats at 1 hr after PCTR1 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Since pulmonary edema can be promoted by decreased expression of alveolar Na-K-ATPase ( Woods et al, 2015 ), drugs or compounds which activate the sodium channel and Na-K-ATPase may be putative therapeutics. Studies have shown that MCTR1 ( Han et al, 2020 ), PCTR1 ( Zhang et al, 2020 ) and protectin DX ( Zhuo et al, 2018 ), endogenously produced lipid mediators, can effectively improve PFC, ameliorate morphological damage, reduce lung inflammation, and increase sodium channel and Na-K-ATPase expression and activity in vivo and in vitro in lipopolysaccharide (LPS)-induced ARDS rats model. Resolving D1 ( Wang et al, 2014 ), generated from ω-3 fatty docosahexaenoic acids, and ursodeoxycholic acid ( Niu et al, 2019 ) can stimulate AFC and Na-K-ATPase in LPS-induced pulmonary edema via alveolar epithelial sodium channel and ALX/cAMP/PI3K pathway, respectively.…”
Section: Putative Drug Targets For Pulmonary Edema In Covid-19 Patientsmentioning
confidence: 99%
“…Since pulmonary edema can be promoted by decreased expression of alveolar Na-K-ATPase ( Woods et al, 2015 ), drugs or compounds which activate the sodium channel and Na-K-ATPase may be putative therapeutics. Studies have shown that MCTR1 ( Han et al, 2020 ), PCTR1 ( Zhang et al, 2020 ) and protectin DX ( Zhuo et al, 2018 ), endogenously produced lipid mediators, can effectively improve PFC, ameliorate morphological damage, reduce lung inflammation, and increase sodium channel and Na-K-ATPase expression and activity in vivo and in vitro in lipopolysaccharide (LPS)-induced ARDS rats model. Resolving D1 ( Wang et al, 2014 ), generated from ω-3 fatty docosahexaenoic acids, and ursodeoxycholic acid ( Niu et al, 2019 ) can stimulate AFC and Na-K-ATPase in LPS-induced pulmonary edema via alveolar epithelial sodium channel and ALX/cAMP/PI3K pathway, respectively.…”
Section: Putative Drug Targets For Pulmonary Edema In Covid-19 Patientsmentioning
confidence: 99%
“…Moreover, PCTR1 generation in peritoneal lavage is decreased in vagotomized mice, suggesting that PCTR1 is controlled by local vagal to improve in ammation resolution [13] . Our previous studies demonstrated that PCTR1 reduced LPS-induced in ammation in mice via regulating linoleic acid metabolism, and improved pulmonary edema uid clearance by activating the sodium channel and lymphatic drainage in LPS-triggered rat model [17,18] . Similarly, we also observed that PCTR1 improved lung function and lung vascular leakage after LPS challenge in mice.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it was shown that one of the fundamental causes of sepsis is the inability to resolve inflammation since promoting the resolution of inflammation in mice with sepsis effectively reduced mortality. 35 , 36 Additionally, lymphatic vessels could effectively transfer inflammatory cells and factors away from tissues and into blood circulation, thereby reducing damage, and promoting the resolution of inflammation. Furthermore, existing research on rat mesentery suggests that Lipopolysaccharide (LPS) modulate neutrophil recruitment and macrophage polarization on lymphatic vessel, thereby impairing lymphatic function.…”
Section: Lymphatic Flowmentioning
confidence: 99%
“…Previous studies from our research group also showed that SPMs could reduce mortality in rats with sepsis and promote the elimination of pulmonary edema fluid as well as inflammatory cells. 36 , 69 Therefore, more studies are needed to establish the therapeutic efficacy of SPMs in promoting the repair and the generation of lymphatics, which will eventually accelerate the resolution of inflammation during sepsis.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%